Microbiological survey of equipment and wheat‐milled fractions of a milling operation. Issue 1 (21st December 2020) - Sabillón, Luis; Stratton, Jayne; Rose, Devin; Bianchini, Andréia
Abstract: Background and objectives: As wheat is milled into flour, there is a substantial risk of cross‐contamination by microorganisms potentially inhabiting the milling equipment. The objectives of this study were designed (a) to assess the levels of microbial contamination associated with the milling equipment and the wheat as it is processed from grain to packaged flour, and (b) to identify equipment that could serve as a source of contamination during processing. Findings: Equipment used to clean and temper wheat grain was found to harbor substantial populations of aerobic mesophilic bacteria, Enterobacteriaceae, and molds. Generic E. coli was found in 2 instances on cleaning equipment at an average of 0.4 log CFU/10 cm 2 . Coliform counts increased markedly in wheat kernels and milled fractions after passing through the different milling steps. Conclusions: These data demonstrate that microorganisms, including fecal indicators, were common colonizers of milling equipment and that a consistent cross‐contamination risk existed throughout the processing line. Cleaning and sanitation efforts should focus especially on tempering equipment and prompt removal of buildup of grain/flour residues within the milling equipment. Significance and novelty: This study identified critical control areas and equipment where cross‐contamination is likely to occur during milling. Appropriate sanitary measures should, therefore, be implemented in the mill to minimize the risk of microbial contamination during wheat milling.